Factors Affecting Customers’ Satisfaction and Perception: Case Study of Islamic Banks’Service Quality - Cheriyah, Yayah; Sulistyowati, Widya; Cornelia, Ade; Viverita, Viverita (UI Scholars Hub, 2021)
This study aims to investigate the perception and expectation of the Islamic bank customers on the banks’ service quality, and how these factors affect their satisfaction and their intention to buy and to use the Islamic banks products and services.This finding implies that the Islamic banks should have pay more attention to their service quality since it would have a positif influence on customer satisfaction and purchase intention.